2021
DOI: 10.1002/ddr.21867
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib weakens resistance of gastric cancer cells to paclitaxel by suppressing JAK/STAT3 signaling pathway

Abstract: Apatinib has experienced a long‐term study in enhancing the sensitivity of various cancer cells to chemotherapy drugs. Currently, researches show that apatinib could attenuate the resistance of gastric cancer (GC) cells to paclitaxel (PTX), but the mechanism has not been fully elucidated, which therefore was explored in this study. PTX‐resistant GC cell, namely HGC‐27R, was established by exposure to stepwise‐increasing PTX. The cell viability of HGC‐27 and HGC‐27R under PTX or apatinib at different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Apatinib has a synergistic effect with chemotherapy and can reverse resistance to chemotherapy. 23, 25, 26 Previous researches revealed that apatinib combined with chemotherapy is more effective compared with apatinib or chemotherapy alone. 13, 27, 28 The combined chemotherapy regimen includes oxaliplatin, FOLFOX, FBC, S-1, taxanes, FOLFIRI, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib has a synergistic effect with chemotherapy and can reverse resistance to chemotherapy. 23, 25, 26 Previous researches revealed that apatinib combined with chemotherapy is more effective compared with apatinib or chemotherapy alone. 13, 27, 28 The combined chemotherapy regimen includes oxaliplatin, FOLFOX, FBC, S-1, taxanes, FOLFIRI, etc.…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2022 ) found that STAT1 is activated in human H. pylori -positive gastritis, whereas STAT1 and its target gene programmed death ligand-1 (PD-L1) are significantly elevated in GC. Bei et al (2022 ) found that apatinib enhances GC cell sensitivity to paclitaxel by inhibiting the JAK/STAT3 signaling pathway. Yang et al (2021 ) observed that STAM2 knockdown may inhibit malignant processes by targeting the JAK2/STAT3 signaling pathway in GC.…”
Section: Introductionmentioning
confidence: 99%